The energy equation : unlocking the hidden power of energy in business - Baker, Greg (Management consultant) (John Wiley & Sons, Inc., 2020)
"The Energy Equation: Unlocking the Hidden Power of Energy in Business makes an important and substantial contribution to management science by helping companies harness the power of professional productivity. Advance Consulting CEO, Greg Baker, details the power of "enterprising" energy, and helps companies build strong organizational health in order to be more effective with clients and customers"--